Off the silk route - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
Mulberry for animal production FAO Animal Production and Health Papers, 2002. 346 pp. ISBN 9251045682 US$ 22 Euro 20.40